Extraordinary magnetic properties of double perovskite Eu2CoMnO6wide band gap semiconductor - Alam, M.; Singh, P.; Anand, K.; Pal, A.; Ghosh, S.; Ghosh, A.K.; Singh, R.K.; Joshi, A.G.; Chatterjee, S. (Institute of Physics Publishing, 2020)
Some novel magnetic behaviours in double perovskite Eu2CoMnO6 (ECMO) have been reported. The x-ray photoemission spectroscopy study shows the presence of mixed valence states of transition metal ions. The UV-visible absorption spectroscopic study suggests that the ECMO has a direct wide band gap. A second-order magnetic phase transition as a sudden jump in the magnetization curve has been observed around 124.5 K. The large bifurcation between the zero field cooling and field cooling, suggests existence of strong spin frustration in the system. The inverse DC susceptibility confirms the presence of the Griffiths like phase. Sharp steps in magnetization have been observed in the M-H curve at 2 K, which vanishes on increasing temperature. The AC susceptibility study demonstrates the Hopkinson like effect as well as the presence of volume spin-glass-like behaviour. The temperature dependent Raman spectrum shows the presence of spin-phonon coupling. © 2020 IOP Publishing Ltd.
Keywords: meta-magnetic transition; Griffiths like phase; spin–phonon coupling; Hopkinson like effect; spin-glass-like behaviour; direct band-gap